If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (10x + 2) + (13x + -25) = z Reorder the terms: (2 + 10x) + (13x + -25) = z Remove parenthesis around (2 + 10x) 2 + 10x + (13x + -25) = z Reorder the terms: 2 + 10x + (-25 + 13x) = z Remove parenthesis around (-25 + 13x) 2 + 10x + -25 + 13x = z Reorder the terms: 2 + -25 + 10x + 13x = z Combine like terms: 2 + -25 = -23 -23 + 10x + 13x = z Combine like terms: 10x + 13x = 23x -23 + 23x = z Solving -23 + 23x = z Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '23' to each side of the equation. -23 + 23 + 23x = 23 + z Combine like terms: -23 + 23 = 0 0 + 23x = 23 + z 23x = 23 + z Divide each side by '23'. x = 1 + 0.04347826087z Simplifying x = 1 + 0.04347826087z
| 3x-5+21x=7(3x+5)+21 | | 3x-5+21x=7(3x+5)21 | | .7x-.5(6-x)=1.2 | | 3y+6=36 | | 100x^2+100x= | | 3m+10=22 | | .4x-.2(4-x)=1.9 | | 4x^2-41x+91=0 | | 2/18a^2x^5 | | 8x-3(3-x)=4(x+3) | | 8x^3-6x^2-23x+4=0 | | 35v/7 | | 5x+65=8x-10 | | b=(5d-c)/d | | -3/10r=-12 | | abs(2x-3)-7=4 | | 4/5=1/3+x | | 6-3(5p+2)= | | 3x+6=211 | | x(x+3)-10=18 | | x^6+x^3-72=0 | | -8m+63-2(m-2)=9m-(2m-9)-6m+3 | | (16x-40)= | | 3x^2-3dx+cx=cd | | 7y+15=4y+17 | | 3/8=b/10 | | Y=-1/2x-11 | | D^2-6d+9=13 | | 5x+2+7x-6=90 | | -8m+36-9(m-1)=5m-(3m-7)-2m+4 | | 9(x-4)+8=4x+5(-5+x) | | 3x-16=7x+2 |